HUMAN-CENTERED DESIGN IN THE PROJECT ACTIVITY OF PUBLIC ORGANIZATIONS - Shpyg, Natalya (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article considers the human-centered design in the project activity of public organizations. The paper reviews scientific works which cover the issues of the human centered design in the human activity.The purpose of the article is to study of the characteristics of the human-centered design in the project activity of public organizations, by specifying human-centered design and clarifying its components its components in accordance with the project format of activity of the public organizations.Theoretical methods of data collection and processing were used to achieve the goal and solve the tasks of the research: analysis, compare, systematization.Emphasized that human-centered design in the project activity of public organizations. is an innovative approach for public organizations to interact with clients: creation of goods, services, social entrepreneurship, social partnership activities. Defining the stage human centered design of for the project activities of public organizations: empathize, define, ideate, prototype, test. Presented is the admission to the approach of the human-centered design in the project activities of the public organizations, on the application of the organization Pact Ukraine within the framework of the project «Women of Ukraine: Heard, Capable, Resilient project».The conclusions indicate that the use of human-centered design in the project activities of public organizations, first of all, characterizes the future project as unique and innovative, which is one of the basic characteristics of the project activity as a whole.The novelty of the study is to determine the content of human-centered design for project activities of public organizations and study the first attempts to practice the use of human-centered design in the development of the concept of project activities of public organizations.